Some Legal Issues Related to the Concepts of Waste in the Republic of Armenia - Geghamyan, Olympia (Bulletin of Yerevan University C: Jurisprudence, 2022)
Emphasizing the role and significance of the impact of waste at the current stage of scientific and technical development and human life, this article presents the analysis of the current situation in the field of concepts of waste management in the Republic of Armenia and their types. The article points out that the main complexity of the sector also lies in the fact that the entire population of the RA is considered the beneficiary and a large number of actors are involved in the management sector.The article discusses the gaps and shortcomings of the sector and their consequences. Effective waste management is of great importance in the public health, environmental, economic, social and cultural spheres of the country, taking into account the long-term and sometimes large-scale nature of its negative consequences.Taking into consideration the role and significance of the national legislation in the field, its impact on practice, appropriate solutions have been proposed.
Keywords: biologocal waste; biodegradable waste; electronic waste; waste hierarchy